Re-engineering Prescription Services as an Alternative Solution - Indriastutik, Nunung; Fitriasari, Nikma; Rusdiana, Dina (Jurnal Kedokteran Brawijaya)
Medication errors could occur at any stage, including prescribing, transcribing, dispensing, and administration stages. Errors in the prescribing stage accounted for the most significant percentage, ranging from 70% to 99%. The most mistake at the prescribing stage is the illegible prescription. This situation causes high morbidity and mortality in hospitals. This study aimed to analyze the root of the problems of the incidence of illegible prescriptions and find anticipating strategies. This research is a descriptive study initiated by finding the root of the problems, followed by identifying alternative solutions and preparing priority solutions. From the analysis of the root of the problems, the illegible prescription included incomplete identity, drug name and the preparation, unclear usage, the error in assuming the writing in the prescription, and ineffective design of the prescription. The solution chosen was the improvement of prescription service flow (re-engineering) that added an identity labeling procedure to correct the error on patient's identity due to the repetition of manual writing and the addition of an authorization procedure by double-checking. The second solution was creating patient identity labels, creating appropriate prescription designs, and developing prescription service guidelines to support the implementation of prescription services re-engineering. This research concludes that the root of the problems on the illegible prescription is the absence of prescription service procedures that aim to anticipate medication errors. Hence, a re-engineering of prescription service needs to be prepared as an alternative solution